Analysis of state and possibilities for profitable prodution of steel in Croatia - Kundak, Mijo (Kovine zlitine tehnologije, 1997)
The production and development of the integrated Sisak Ironworks since 1973 are presented. The Ironworks participates with 80% in the total rolling stock production in Croatia. The development of the world steel production is presented and compared to the circumstances in Croatia. The feasible manufacture level of rolled products in Croatia is shown and discussed considering the low price steel manufacturing in electric arc furnaces. A comparison between the production in electric arc furnace and a feasable steel manufacture in existing blast furnaaces and converters with enlaarged share of steel scrap is prepared with the aim to contribute to a better insight into the possibilities of a more profitable steel manufacturing in Croatia.
Keywords: proizvodnja jekla; železarne; Sisak; Croatia; Hrvatska